The Consumption of Energy Drink and Its Potential Effect on Sleep Patterns: A Case Study in the Kumasi Metropolis - Christopher Sarpong; Marcel Tunkumgnen Bayor; Raphael Johnson; Maruf Abbdullai; Mariam EL Boakye-Gyasi; Stephen Yao Gbedema; Frederick William Akuffo Owusu (Research Center for Rational Use of Drugs (RCRUD), 2023)
Background: The availability of energy drinks on the global market result from intensive marketing campaigns in the media. The purpose of this study was to evaluate the consumption of energy drink and its potential effect on sleep patterns of consumers. Methods: A descriptive cross-sectional design with self-administered questionnaire was used for this survey. An online survey using google forms was created for the validated questionnaires after pre-testing and the link shared on different social media platforms. Period of data collection lasted between January and September, 2020. Results: A total of 384 participants were involved in this study. From the study, prevalence of energy drink consumption in the metropolis is 61.5% (n=236). A percentage of 69.1 % (n=163) of the consumers are males relative to 30.9% (n=73) who are females. Results from the study indicate that most patronized energy drink in the metropolis has energy value per 100 ml of 158 kJ with no proteins and fats but an 8.9 g of carbohydrate. The caffeine content of this energy drink is 0.012% and 13% glucose syrup. A total of 29.6% (n=70) of energy drink consumers indicated it to be their preference. Least consumed energy drink (0.85%) has 30-35 mg/100 ml of caffeine with about 192 kJ energy value. Furthermore, results point out that 70.8% (n=167) of the consumers experienced change in sleep pattern. Although other factors may have caused this change in sleep pattern, Pearson Chi-Square result (x2 = 83.277, p≤0.01) reveals that indeed there is association between energy drink consumption and change in sleep pattern as majority of energy drink consumers indicated that they usually experience changes in wake-up time and/or bedtime. Conclusion: The study has demonstrated that majority of the youth in the Kumasi Metropolis consume energy drinks which ultimately causes change in their sleep pattern. This change can alter their daily activities and health status.